Impact Of Magnetised Water on Nigeria Broiler Chicken Performance and Growth Rate - Adebayo Tajudeen BAKER; O. I. OJO; M. O. DINKA; S. RWANGA (Journal of Digital Food, Energy & Water Systems)
Poultry farming is vital to Nigeria’s economy and provides a key protein source, yet many farms struggle with slow growth and high mortality in broiler chickens. This study aimed to assess the impact of magnetised water on broiler growth.